Quantitative prediction of histamine H1 receptor occupancy by the sedative and non-sedative antagonists in the human central nervous system based on systemic exposure and preclinical data. Issue 2 (April 2017) - Kanamitsu, Kayoko; Nozaki, Yoshitane; Nagaya, Yoko; Sugiyama, Yuichi; Kusuhara, Hiroyuki
Abstract: Significant histamine H1 receptor occupation in the central nervous system (CNS) is associated with sedation. Here we examined the time profiles of the H1 receptor occupancy (RO) in the CNS using sedative (diphenhydramine and ketotifen) and non-sedative (bepotastine and olopatadine) antagonists at their therapeutic doses by integrating in vitro and animal data. A pharmacokinetic model was constructed to associate plasma concentrations and receptor binding in the brain. Dissociation and association rate constants with the H1 receptor and plasma and brain unbound fractions were determined in vitro . Passive and active clearances across the blood–brain barrier (BBB) were estimated based on physicochemical properties and microdialysis studies in mice and monkeys. The estimated RO values were comparable with the reported values determined at time to maximum concentration (Tmax ) of plasma by positron-emission tomography in humans. The simulation suggested that the predicted maximum ROs by bepotastine and olopatadine were greater than the reported values. Sensitivity analysis showed that active transport across BBB had a significant impact on the RO duration of the H1 antagonists examined. The present study demonstrated that modeling and simulation permits a reasonable RO estimation in the human CNS. Our findings will facilitate the development of CNS-acting drugs. Graphical abstract: